(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Amateur and professional sports organizations serve distinct purposes within the sports ecosystem. Amateur organizations focus on participation, skill development, and enjoyment of sports without financial gain as the primary motive. They are typically organized at local, regional, or national levels and include clubs, schools, colleges, and community programs. Funding for amateur sports often comes from membership fees, donations, grants, and sponsorships. Examples include Little League Baseball and the NCAA